2021
DOI: 10.1002/jclp.23123
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between negative emotional eating and binge eating: The moderating effects of acting with awareness and non‐reactive mindfulness

Abstract: Objectives Negative emotional eating and binge eating are positively related, occur in diverse populations, and may be driven by similar mechanisms. Mindfulness facets such as acting with awareness, describe, non‐judgement, non‐reactive, and observe may moderate the relationship between these maladaptive eating phenotypes. Method A cross‐sectional study assessed emotional eating‐depression (Emotional Eating Scale‐Revised, depression subscale), trait mindfulness facets (Five Facet Mindfulness Questionnaire‐Shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 79 publications
(139 reference statements)
5
14
1
Order By: Relevance
“…In an online community sample with overweight weight status, higher acting with awareness, describe, and non-judgment, but not non-reactive and observe, mindfulness facets were associated with lower negative emotional eating [25]. Interestingly, other research has suggested that more external/sensory-based facets of mindfulness such as observe may be positively associated with negative emotional eating [25,[26][27]. Consistent with that theory, using a longitudinal approach, one study identi ed that higher observe mindfulness assessed at baseline was predictive of worsened external eating and negative emotional eating six months later [27].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In an online community sample with overweight weight status, higher acting with awareness, describe, and non-judgment, but not non-reactive and observe, mindfulness facets were associated with lower negative emotional eating [25]. Interestingly, other research has suggested that more external/sensory-based facets of mindfulness such as observe may be positively associated with negative emotional eating [25,[26][27]. Consistent with that theory, using a longitudinal approach, one study identi ed that higher observe mindfulness assessed at baseline was predictive of worsened external eating and negative emotional eating six months later [27].…”
Section: Introductionmentioning
confidence: 80%
“…One study identi ed that higher acting with awareness, describe, non-judgment, and non-reactive, but not observe, mindfulness facets were associated with lower negative emotional eating in a pre-surgical bariatric population [24]. In an online community sample with overweight weight status, higher acting with awareness, describe, and non-judgment, but not non-reactive and observe, mindfulness facets were associated with lower negative emotional eating [25]. Interestingly, other research has suggested that more external/sensory-based facets of mindfulness such as observe may be positively associated with negative emotional eating [25,[26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Some factors that play a role in creating emotional eating are lower parental quality in infancy [ 6 , 7 ], parental rejection [ 8 ], or childhood invalidation and emotional reactivity [ 9 ]. The side effects of emotional eating include overeating and binge eating, with the latter being linked to a more serious eating disorder [ 10 , 11 ] or depression and weight gain [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…parental rejection [8], or childhood invalidation and emotional reactivity [9]. The side effects of emotional eating include overeating and binge eating, with the latter being linked to a more serious eating disorder [10,11] or depression and weight gain [12].…”
Section: Introductionmentioning
confidence: 99%